PEMIKIRAN POLITIK SUTAN SJAHRIR TENTANG SOSIALISME SEBUAH ANALISIS PSIKOLOGI POLITIK - Pramasanti, Restuning (Journal of Politic and Government Studies, 2013)
AbstractThis research is used to explain Sutan Sjahrir’s development process of Socialism thought, and which psychological factors that influenced it.The type of reasearch is historical descriptif, because the subjects is a deceased character. Thus, this kind of reasearch is library research which is used to analyze datas such as books, journals, articles and other results of previous reasearch about Sutan Sjahrir’s life and thought that still considered as a relevant. Those datas were sistematically refined so that the result of the research can be earned as expected.The research showed that the psychological factors which have influenced Sutan Sjahrir’s thought of Socialism are his avidity reading Socialism books, European eagerness after World War I, his interaction with the Socialist in Netherland and also his activities in many Socialist organizations. As for a character who influenced him the most was Karl Marx.For Sutan Sjahrir, Socialism is supposed to be based on people. Socialism for humanity, by recognizing the equality of people. His thought about this is used as political fundamental of Partai Sosialis Indonesia he formed.